Tetranychidae (acari) in forest fragments in the state of São Paulo, Brazil - Demite, Peterson R. [UNESP]; Flechtmann, Carlos H. W.; Feres, Reinaldo J. F. [UNESP] (Les Amis d'Acarologia, 2016)
Tetranychidae is an important family of phytophagous mites, with some species considered agricultural pests. Nevertheless, there are few studies about the diversity of this mite family in natural environments. Thus, the objective was to record the species of spider mites associated with plants in forest fragments located in the Northwestern of the State of São Paulo, Brazil. Thirty-eight species belonging to 14 genera of Tetranychidae were recorded. Only Tetranychus mexicanus and Eutetranychus banksi, species recorded on plants of economic interest, in some cases causing damage to crops, were abundant and frequent in the forest fragments sampled in this study. The knowledge of plants that can serve as alternate hosts or plant-traps can assist in understanding the dynamics of these mites in agroecosystems. The great diversity of Tetranychidae registered, and the limited knowledge of these mites associated with plants in natural environments, reinforces the importance of surveys carried out in forest remnants. Future studies should be conducted to increase the knowledge of spider mites in natural areas.
Keywords: Conservation; Forest remnants; Phytophagous mites